Uma democracia contra o povo: Juraci Magalhães, Otávio Mangabeira e a UDN na Bahia (1927 – 1946) - Lima, Aruã Silva de (2010)
This dissertation is about the trajectory of two political groups that built a controversial political alliance. Juraci Magalhães and Otávio Mangabeira are structuring axis of this work. The disposition of this dissertation is divided in four chapters and the first one is a short exposition of Juraci Magalhães and Otávio Mangabeira’s trajectory. The second one assesses the construction of liberalism in Bahia in dialog with other regional expression and, also, with interaction strategies with international groups. The third chapter refers to anticommunism, a fundamental compound of UDN, as agglutinating factor of leading classes whose divergences were minimized when they faced “populism” of Vargas and the advance of PCB. The fourth chapter highlights the importance of these two agents of the Americanism forged in this country. Mainly it is about the second half of the 30’s and it analyzes how they both influenced on the construction of liberalism and anticommunism invented in Brazil. The relevance of this work, then, is situated on the historicizing of the liberal ethics of a leading local group with national influence.